Frequencies in plant physiology: enhancing nutrient uptake and protocol for frequency acquisition in soybean - Miotti, Fernanda (2025)
This study explores the emerging field of phytoacoustics, which investigates the ability of plants to perceive, emit, and respond to sound and frequency stimuli, including their electrical responses. The first part of the study focused on advancing phytoacoustic methodologies by developing a standardized protocol for frequency acquisition in plants. An anechoic chamber was designed and constructed using sound-absorbing materials to create a controlled environment for capturing acoustic signals emitted by plants, primarily in the ultrasonic range, under stress conditions. The integration of the PlantWave device with an oscilloscope and an Arduino microcontroller successfully translated the plants\' bioelectrical signals into audio output, providing new insights into plant-environment interactions through electrical responses. In the second part of this research, we evaluated the effects of Extremely Low Frequencies (ELF) combined with different concentrations of nutrient solutions on the morphophysiological parameters of soybean plants during the vegetative stage. The results showed that ELF treatment significantly increased chlorophyll content, especially under the TB treatment, suggesting improved nutrient use efficiency and enhanced metabolic activity. These findings highlight the potential of ELF as a tool for sustainable agricultural practices that support plant health even under suboptimal nutrient conditions. This study provides valuable insights into the acoustic and electrical responses of plants and demonstrates the potential of ELF to optimize plant physiological responses, offering a sustainable approach to improving crop productivity and resource use efficiency in agriculture.